Interactions between systemic diseases and oral microbiota shifts in the aging community: A narrative review - Mosaddad, Seyed Ali; Mahootchi, Pegah; Safari, Sajedeh; Rahimi, Hussein; Aghili, Seyedeh Sara (Journal of basic microbiology, 2023)
As a gateway to general health and a diverse microbial habitat, the oral cavity is colonized by numerous microorganisms such as bacteria, fungi, viruses, and archaea. Oral microbiota plays an essential role in preserving oral health. Besides, the oral cavity also significantly contributes to systemic health. Physiological aging influences all body systems, including the oral microbial inhabitants. The cited effect can cause diseases by forming dysbiotic communities. Since it has been demonstrated that microbial dysbiosis could disturb the symbiosis state between the host and the resident microorganism, shifting the condition toward a more pathogenic one, this study investigated how the oral microbial shifts in aging could associate with the development or progression of systemic diseases in older adults. The current study focused on the interactions between variations in the oral microbiome and prevalent diseases in older adults, including diabetes mellitus, Sjögren's syndrome, rheumatoid arthritis, pulmonary diseases, cardiovascular diseases, oral candidiasis, Parkinson's disease, Alzheimer's disease, and glaucoma. Underlying diseases can dynamically modify the oral ecology and the composition of its resident oral microbiome. Clinical, experimental, and epidemiological research suggests the associations of systemic disorders with bacteremia and inflammation after oral microbial changes in older adults.